RANCANG BANGUN TEMPAT SAMPAH PINTAR MENGGUNAKAN SENSOR JARAK BERBASIS MIKROKONTROLER ARDUINO - Fatmawati, Kiki; Sabna, Eka; Muhardi; Irawan, Yuda (Riau Journal Of Computer Science, 2020)
Garbage is a serious threat to humans, because littering can cause environmental pollution. Poor waste management has an impact on environmental problems. In this problem, it is necessary to have a smart trash can based on the Arduino Microcontroller which includes the HC-SR04 Ultrasonic Sensor as a distance detector and a trash volume detector, a Servo is used to control the lid of the trash, a Capacitive Proximity Sensor is used to sort organic and inorganic waste types, Buzzers and LED as an alarm and a sign that the trash can is full, and the GSM SIM800L V.2 Module which is used to give SMS to officers that the trash can is full. The smart trash can has two spaces for organic and inorganic waste and has one entrance for disposing of trash. The smart trash lid will open and close automatically by detecting the presence of humans with a distance of 40 cm, if the trash is detected by organic waste, the servo will move to the left of the organic waste bin. Conversely, if it is not detected by a capacitive proximity sensor, the servo will move to the right of the inorganic trash. When the trash can is full, the buzzer sounds and the LED lights up, and sends an SMS to the officer that the trash can is full